When patients decide the admission - a four year pre-post study of changes in admissions and inpatient days following patient controlled admission contracts - Olav Nyttingnes; Torleif Ruud (BMC, 2020)
Abstract Background Mental health professionals usually decide patients' access to inpatient care to ensure the rational and fair distribution of care based on need and prognosis. The purpose of the current study is to investigate the effects of increasing patients' influence on admission by enabling patients to initiate brief inpatient stays of up to five days at a community mental health center. Patients can initiate admission according to their own discretion, outside the existing referral and gatekeeping system. Methods Patient-controlled admission (PCA) contracts were offered to eligible patients for inpatient stays in four community mental health centers in one health trust in Norway. Data on included patients' inpatient stays at any of the hospitals' mental health or addiction wards were collected by hospital electronic journal data extraction specialists for the two years before PCA contracts were introduced and the first two years after PCA contracts were introduced for the included patients. Results The included patients (n = 57) had 406 PCAs in the two years following signing PCA contracts. When comparing the periods before and after the introduction of the contracts, the total number of admissions increased from 203 to 498 (p < .001), while the number of inpatient days decreased from 7172 to 3178 (p < .001). No significant change in involuntary care was observed. A comparison of box plots of inpatient day use in the eight half-year periods of the study indicates a gradual increase in median inpatient days up to the signing of a PCA contract for the sample, and an abrupt reduction to a stable median level of inpatient days after signing a contract. Conclusions The included patients' use of inpatient days changed profoundly after signing PCA contracts, similar to what previous studies of PCAs have indicated. In spite of the marked reductions in inpatient days, the pre-post design makes it impossible to rule out that the reductions were caused by regression toward the mean. No study of PCAs has reported negative effects, indicating that giving patients control over very short admissions is a feasible and potentially positive scheme in mental health care wards.